A circular : 1 - Proença, Pedro; Martins, Alfonso ([s.l.] : A Circular, 2011)
Contents##The Chair of Decency by Stefan Themerson ##Never Odd or Even by Fay Nicolson ##Under the Counter-Culture by Robin Fior ##The Impostor by Nathanael West ##Open Letter to Monotype by Open Source Publishing ##A Knight in the White House, A Quarrel with a Post Marxist by Mathew Whittington ##Middle of Nowhere (continued) by Will Holder ##Notes of intention for a letter to the film by Maël Fournier-Comte ##Throwing A Rubber Band in the Air by Xavier Antin
boek